Repeat pneumothorax as the First Clinical Manifestation of Birt-Hogg-Dubé Syndrome: Case Report (Revista de Medicina Clinica, 2022)
The Birt Hogg Dube síndrome is a rare autosomal dominant inheritance condition. The most frequent clinical presentation are cutaneous lesions and, later on kidney and pulmonary manifestations. We report the case of a 33-year-old patient with recurrent spontaneus pneumothorax treated with surgery. Although Birt Hogg Dube síndrome is rare, it should be considered as part of the differential diagnosis of spontaneus and recurrent pneumothorax to complete the study and follow-up.